Evaluation of Sperm DNA Peroxidation in Fertile and Subfertile Dogs - Lopes-Santiago, B. V. [UNESP]; Monteiro, G. A. [UNESP]; Bittencourt, R. [UNESP]; Arduino, F.; Ovidio, P. P.; Jordao-Junior, A. A.; Araujo, J. P. [UNESP]; Lopes, Maria Denise [UNESP] (Wiley-Blackwell, 2012)
Contents Oxidative stress (OS) has been recognized as one of the most important causes of male infertility. The antioxidant activities of seminal plasma and epididymal fluid are not enough to prevent OS, which can damage sperm membranes and DNA, so antioxidant supplementation has been used as a treatment of male infertility. The aim of this experiment was to evaluate the DNA peroxidation before and after antioxidant supplementation with vitamin C and E in dogs with and without fertility problems. A total of eleven dogs were used and were divided in two groups: fertile group (G1), dogs with normal spermiogram (n=5); subfertile group (G2): dogs with low sperm count (<20x106sptz/ml) and/or more than 30% of total sperm pathology (n=6). Both groups received 500mg/day of vitamin C and 500mg/day of vitamin E for 60days. A semen sample was collected before (M1) and after (M2) oral supplementation. Samples were analysed for DNA peroxidation by measuring the 8-hydroxy-2'-deoxyguanosine concentration. No significant difference was observed between groups at either time. Oral supplementation with 500mg/day of vitamin C and 500mg/day of vitamin E did not change the DNA peroxidation in fertile and subfertile dogs.